Visually identifying the sex of a bird can be difficult. It cannot be done in half the world’s species when they are adults, and virtually none can be sexed as chicks. Despite this, the sex of a bird is vital for captive breeding. An increased number of birds are being sexed using DNA amplification techniques. In this approach, the CHD-W and CHD-Z are distinguished by the amplification of an intron present in both genes. PCR products on the gel electrophoresis vary in size revealing one band in - SRI SULANDARI; MOCH SYAMSUL ARIFIN ZEIN (Bogor Agricultural University, Indonesia, 2012)
Visually identifying the sex of a bird can be difficult. It cannot be done in half the world’s species when they are adults, and virtually none can be sexed as chicks. Despite this, the sex of a bird is vital for captive breeding. An increased number of birds are being sexed using DNA amplification techniques. In this approach, the CHD-W and CHD-Z are distinguished by the amplification of an intron present in both genes. PCR products on the gel electrophoresis vary in size revealing one band in males at the CHD-Z, and two bands in females corresponding to both the CHD-W and CHD-Z. Two independent sets of primer (P8/P2 and 2550F/2718R) were used to amplify the CHD gene region from both the Z and W chromosome. One hundred and ten (110) birds were sexed using first pair of primers: (P8/P2). Sexing results indicated that 81.8% were successfully determined, 12.7% failed to be amplified and 5.5% were not perfectly determined because the PCR products showed thick band. The thick band caused misidentified female to male birds. An alternative primer (2550F/2718R) was applied to solve the problem. Two hundreds and twenty-nine birds were sexed and the results showed 100% successfully determined. From this study, it is suggested to use a pair of 2550F and 2718R primers for distinguishing a male from a female bird.